UJI AKTIVITAS ANTIDIARE EKSTRAK ETANOL KULIT BATANG SENGKUANG Dracontomelon dao (Blanco) Merr & Rolfe TERHADAP MENCIT PUTIH (Mus musculus) JANTAN DENGAN METODE PROTEKSI DIARE - Inderiyani Inderiyani; Sulastri Sulastri (Jurnal Insan Farmasi Indonesia, 2021)
Sengkuang Dracontomelon dao (Blanco) Merr & Rolfe is a plant that has secondary metabolites tannins and flavonoids which are thought to have anti-diarrheal activity. The purpose of this study to determine activity and dose of ethanol extract of the stem bark of Dracontomelon dao (Blanco) Merr & Rolfe which has antidiarrheal effect on male white mice (Mus musculus). The antidiarrheal activity test was using the diarrhea protection method, where mice were induced by 0.75 mL of oleum ricini orally, 1 hour later the test solution was given i.e. 0.5% Na CMC suspension (negative control), loperamid 0.26 mg/kg bw (positive control), dose of sengkuang stem bark ethanol extract 100 mg/kg bw, 200 mg/ kg bw and 300 mg/kg bw. Then observed the onset of diarrhea, frequency of diarrhea, consistency of diarrhea, duration of diarrhea and weight of diarrhea every 30 minutes for 4 hours. The results is the ethanol extract of the stem bark Dracontomelon dao (Blanco) Merr & Rolfe at a dose of 100 mg/kg bw, 200 mg/kg bw and 300 mg/kg bw has antidiarrheal activity as indicated by a significant difference in the test group (control positive and all extracts) against the negative control group (p <0.05).